Guided self-assembly method of polymer composition and film thereof

By introducing bottle brush-like polymer additives into high-χ block copolymers to balance their surface free energy, the problem of block copolymers being difficult to form vertical nanostructures is solved, and efficient and economical nanostructure self-assembly is achieved, which is suitable for semiconductor device manufacturing.

CN119775703APending Publication Date: 2025-04-08CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411904936.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the case of high χ value and large surface free energy difference between the two blocks, it is difficult to form vertically oriented nanostructures, which limits its application in semiconductor device manufacturing.

Method used

By introducing polymer additives with low content of bottle brush-like topological structures, the interaction between block copolymers and high χ block copolymers is enhanced, and their surface free energy is balanced, thereby inducing vertically oriented nanostructures.

Benefits of technology

The high χ value block copolymer is quickly self-assembled under low temperature conditions, and an ordered nanostructure perpendicular to the substrate is obtained, which simplifies the process flow, improves production efficiency, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a polymer composition and a guided self-assembly method of a film of the polymer composition, and belongs to the technical field of guided self-assembly. The polymer composition comprises the following components in percentage by mass: 70wt%-99.8 wt% of a high-x-value block copolymer A-b-B, 9wt%-9wt% of a high-x-value block copolymer A-b-B; 0.1 wt% to 15 wt% of an additive I; 0.1 wt% to 15 wt% of an additive II; the sum of the dosages of all the components is 100wt%. According to the polymer composition disclosed by the invention, an ordered nanostructure which is vertical to a substrate and penetrates through the thickness of a whole film can be obtained through a guided self-assembly method, and the nanostructure can be transferred to the substrate through etching. Therefore, the block copolymer with high chi value and large difference between the two blocks gamma is easier to obtain an ideal vertical ordered nanostructure, and a new thought is provided for obtaining a substrate structure with a smaller size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of guided self-assembly, in particular to a guided self-assembly method of a polymer composition and a film thereof. Background Art

[0002] The guided self-assembly (DSA) technology of block copolymers has attracted widespread attention as an alternative to ultra-high-resolution patterning. Block copolymers are composed of different polymer segments, which are linked together by covalent bonds. Different polymer segments repel each other, and microphase separation occurs at the microscopic level, forming an ordered structure with a size range of 5 to 100 nanometers. In the film, the phase domains formed by block copolymers can be arranged into long-range ordered lattices, lines, etc. These structures can be accurately transferred and etched onto the substrate and applied to the manufacture of nanodevices.

[0003] Block copolymer lithography requires the formation of vertically oriented columnar or lamellar phases with connectivity and high aspect ratio during pattern transfer operations, which requires that the surface free energy (γ) of the two blocks in the block copolymer be similar and the substrate be neutralized so that the air surface and substrate interface can non-selectively wet both blocks.

[0004] The excellent properties of PS-b-PMMA make it the "gold standard" in DSA research, but its minimum phase separation period (L 0 ) is too large to meet the manufacturing requirements of ≤7nm nodes. In order to obtain a smaller L 0 , the χ value of the block copolymer should be as large as possible. Increasing the χ value of the diblock copolymer can generally be changed by adjusting the monomer structure of the block copolymer. However, the introduction of these groups will increase the surface free energy difference between the blocks, resulting in the domains in the film being easily selectively wetted on the air surface or substrate interface. It is almost impossible to form a vertically penetrating domain structure only by thermal annealing, making this type of high χ value block copolymer difficult to be used in the manufacture of semiconductor devices.

[0005] In order to overcome the problem of large differences in surface free energy of block copolymers, a solvent annealing method was developed. Its main principle is to increase the mobility of polymer chains by exposing block copolymer films to solvent vapor, thereby promoting the self-assembly process. It can be carried out at a lower temperature to avoid thermal degradation; achieve rapid self-assembly; and obtain a vertically oriented structure. However, its process control is difficult, and parameters such as solvent concentration and annealing time need to be precisely controlled, otherwise it is easy to cause structural defects. The film swelling caused by the solvent will cause structural deformation, and the film will collapse when the solvent is removed quickly. After annealing, the solvent needs to be removed slowly to solidify the formed structure. It is difficult to completely remove the solvent, and the residual solvent will affect subsequent processing and device performance. Some solvents may react adversely with the substrate or other layers, and the type of solvent is difficult to select. It is difficult to uniformly control the solvent concentration and distribution on a large-area substrate.

[0006] The top-coating process is to use the coating material to form an open-loop state in an aqueous solution, and then apply the solution to the block copolymer film surface by spin coating; then the polarity is changed by heating the closed loop, thereby balancing the surface free energy and inducing the vertical orientation of the block copolymer; after annealing, the coating can be removed with an alkaline solution to expose the vertically oriented nanostructure. This method can achieve large-area uniform coating, is compatible with the existing thermal annealing process, and induces the vertical orientation of high-χ block copolymers. However, specific coating materials need to be designed for different block copolymer systems, which lacks versatility; additional steps such as coating, annealing, and coating removal are added, which increases the complexity of the process; some systems (such as PTMSS-PLA) require a long annealing time (20 hours), which affects production efficiency; there may be mutual diffusion between the coating and the block copolymer, which affects the precise control of the interface; the coating removal process is prone to damage the underlying nanostructure.

[0007] The addition of inorganic nanoparticles can also improve the self-assembly process of block copolymers and obtain vertical structures. The main principle is to add inorganic nanoparticles to block copolymers and use the interaction between nanoparticles and specific blocks to affect the self-assembly process. Adding appropriate inorganic nanoparticles can enhance long-range order, reduce defects, and induce the formation of vertical structures. However, the introduction of nanoparticles makes the system more complicated and increases the difficulty of process control. Nanoparticles are difficult to disperse evenly in polymers, resulting in local inhomogeneities. For electronic device applications, nanoparticles will affect the electrical properties of the material. Nanoparticles are difficult to be stable in polymers for a long time and may agglomerate to have an impact.

[0008] By adding polymers, balancing the surface free energy, inducing vertical orientation to obtain an ideal structure. The high-χ block copolymers based on P2VP-b-PS-b-P2VP (VSV) reported in the current study can achieve smaller feature sizes, but it is difficult to form a vertically oriented nanostructure due to the large difference in surface energy between the PS and P2VP blocks. By adding a fluorinated polymer additive (PHFAS) and adjusting the amount of PHFAS in the system, the surface energy of the PS and P2VP blocks can be effectively balanced, and the desired vertical orientation can be formed after thermal annealing. However, the polymer additive mainly forms hydrogen bonds with the P2VP component in the block copolymer, and its ability to influence the assembly process is limited. When the additive amount is too high, it is easy to locally aggregate and produce defects; when the additive amount is too low, it cannot provide a stable upper surface and cannot obtain an ideal vertical structure. In addition, it is difficult for PS-type polymers to form intermolecular forces similar to hydrogen bonds, and there is no suitable additive to balance the surface energy; at the same time, due to the lack of additives suitable for PS, the swelling process is asymmetric, and swelling only P2VP will affect the symmetry of the pattern. Therefore, this method has limitations and cannot be widely used.

[0009] Therefore, it is of great significance to study and develop a new patterning method for block copolymers with high χ values ​​and large differences in the γ phases of the two blocks to obtain an ideal vertical structure. Summary of the invention

[0010] In view of this, the technical problem to be solved by the present invention is to provide a polymer composition and a guided self-assembly method of a film thereof. The polymer composition can obtain an ordered nanostructure perpendicular to a substrate and throughout the entire thickness of the film through guided self-assembly, and the nanostructure can be transferred to the substrate through etching.

[0011] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0012] The present invention provides a polymer composition, which comprises the following components by mass percentage:

[0013] High χ value block copolymer AbB: 70wt%-99.8wt%;

[0014] Additive I: 0.1wt%-15wt%;

[0015] Additive II: 0.1wt%-15wt%;

[0016] The sum of all components is 100wt%;

[0017] The high-χ value block copolymer AbB has a χ value>0.05, and the surface free energy of block A is γ A >30mJ / m 2, the surface free energy of block B γ B >30mJ / m 2 The absolute value of the surface free energy difference between the two blocks is greater than 5 mJ / m 2 ;

[0018] The high-χ value block copolymer AbB has a number average molecular weight of 5k-50k, and a volume fraction of block A of 20%-80%;

[0019] The additives I and II are polymers AC and BC, respectively, and both have bottle-brush-like topological structures;

[0020] The surface free energy of C in the polymers AC and BC is γ C <30mJ / m 2 And it does not react with A or B.

[0021] The polymer composition of the present invention enhances the interaction between the additive and the high-χ value block copolymer AbB through a low content of the additive, provides a stable polymer-air interface, and balances the surface free energy of the high-χ value block copolymer AbB.

[0022] Preferably, the contents of the additive I and the additive II are independently selected from 1 wt% to 10 wt%.

[0023] Preferably, the high-χ value block copolymer AbB is selected from one or more of styrene derivative-b-polyvinyl pyridine, polystyrene derivative-b-polyacrylate derivative, polyvinyl condensed ring-b-polyacrylate derivative, and polyvinyl alicyclic-b-polyacrylate derivative.

[0024] Preferably, the high x-value block copolymer AbB is selected from one or more of polystyrene-b-poly(2-vinylpyridine) (PS-b-P2VP), poly(4-tert-butylstyrene)-b-poly(2-vinylpyridine) (PtBS-b-P2VP), polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP), polystyrene-b-polycarbonate acrylate (PS-b-PPC), polystyrene-b-polyglycerol monomethyl methacrylate (PS-b-PGM), polymethylstyrene-b-polymethyl methacrylate, polydimethylstyrene-b-polymethyl methacrylate, poly-4-vinylbiphenyl-b-polymethyl methacrylate, polymethylstyrene-b-polymethyl acrylate, polydimethylstyrene-b-polymethyl acrylate, poly-4-vinylbiphenyl-b-polymethyl acrylate, polyvinylnaphthalene-b-polymethyl methacrylate (PVN-b-PMMA), and polycyclohexylethylene-b-polymethyl methacrylate (PCHE-b-PMMA).

[0025] Preferably, the number average molecular weight of the high χ value block copolymer AbB is 5k-20k.

[0026] Preferably, in the polymers AC and BC, C is selected from fluorine-containing polymers, silicon-containing polymers, C 16 -C 32 Alkanes or C 10 -C 32 of perfluorinated alkanes.

[0027] Preferably, the polymer AC is selected from A-stat-C or A-branch-C;

[0028] Preferably, the polymer BC is selected from B-stat-C or B-branch-C.

[0029] The A- stat -C or B- stat -C are obtained by random copolymerization of macromonomers A and C, or macromonomers B and C, respectively.

[0030] The A- branch -C or B- branch -C are composed of macromonomers A- b -C or macromonomer B- b -C homopolymerization.

[0035] Preferably, C in the polymer AC and the polymer BC is selected from a fluorine-containing polymer or a silicon-containing polymer.

[0036] Preferably, the backbone chain polymerization degree of A-stat-C and B-stat-C is independently selected from 2-50, wherein the number average molecular weights of macromonomer A, macromonomer B and macromonomer C are independently selected from 1k-10k, and the volume fraction of C in polymer A-stat-C or B-stat-C is 30%-70%.

[0037] More preferably, the backbone chain polymerization degrees of the A-stat-C and B-stat-C are independently selected from 2-20;

[0038] More preferably, the number average molecular weights of the macromonomer A, macromonomer B and macromonomer C are independently selected from 1k-5k;

[0039] More preferably, the volume fraction of C in polymer A-stat-C or B-stat-C is 40%-60%.

[0040] Preferably, the backbone chain polymerization degree of A-branch-C and B-branch-C is independently selected from 2-50, wherein the number average molecular weight of the macromonomer AbC or BbC is independently selected from 1k-20k, and the volume fraction of C in A-branch-C and B-branch-C is 30%-70%.

[0041] More preferably, the backbone chain polymerization degrees of the A-branch-C and B-branch-C are independently selected from 2-20;

[0042] More preferably, the number average molecular weight of the macromonomer AbC or BbC is independently selected from 1k-10k.

[0043] Alternatively, it is preferred in the present invention that the polymer AC is selected from A-stat-C or A-branch-C;

[0044] The polymer BC is selected from B-stat-C or B-branch-C;

[0045] Preferably, C in the polymer AC and the polymer BC is selected from C 16 -C 32 Alkanes or C 10 -C 32 Perfluoroalkanes;

[0046] Preferably, the backbone chain polymerization degree of the A-stat-C and B-stat-C is independently selected from 2-50, wherein the number average molecular weight of the macromonomer A and the macromonomer B is independently selected from 1k-10k, and the volume fraction of C in the polymer A-stat-C or B-stat-C is 1%-40%;

[0047] More preferably, the number average molecular weights of macromonomer A and macromonomer B are independently selected from 1k-5k,

[0048] More preferably, the volume fraction of C in polymer A-stat-C or B-stat-C is 10%-30%.

[0049] Preferably, the backbone chain polymerization degrees of the A-branch-C and B-branch-C are independently selected from 2-50, wherein the number average molecular weight of the macromonomer AbC or BbC is independently selected from 1k-10k; more preferably 1k-5k.

[0050] Preferably, the fluorine-containing polymer is selected from one or more of polypentafluorostyrene (PPFS), polyperfluoroalkyl methacrylate, and polyperfluoroalkyl acrylate;

[0051] The polyperfluoroalkyl methacrylate includes but is not limited to polyhexafluorobutyl methacrylate (PHFBMA), poly[2-hydroxy-3-(2,2,2-trifluoroethylsulfanyl) propyl methacrylate] (PHFMA) and poly(2,2,2-trifluoroethyl methacrylate) (PTFEMA), etc.;

[0052] The polyperfluoroalkyl acrylate includes but is not limited to polyhexafluorobutyl acrylate (PHFBA) and the like.

[0053] Preferably, the silicon-containing polymer is selected from one or more of polydimethylsiloxane (PDMS), polymethylphenylsiloxane, poly(4-trimethylsilylstyrene), poly(dimethylsiloxane-co-methylphenylsiloxane), poly(dimethylsiloxane-co-diphenylsiloxane), and polymethylphenylsiloxane; more preferably, one or more of polydimethylsiloxane, poly(4-trimethylsilylstyrene), and polymethylphenylsiloxane.

[0054] Preferably, the alkane is selected from C 16 -C 32 An alkane wherein the number of C is an even number; specifically including but not limited to n-hexadecane, n-octadecane, n-eicosane, n-docosane, n-tetracosane or n-hexacosane.

[0055] Preferably, the perfluoroalkane is selected from C 10 -C 32 A perfluoroalkane wherein the number of C is an even number; more preferably C 18 -C 26 Perfluoroalkanes, including but not limited to perfluoro-n-octadecane, perfluoro-n-docosane or perfluoro-n-hexacosane.

[0056] The present invention also provides a method for guiding self-assembly of a polymer composition film, comprising the following steps:

[0057] A solution containing the above polymer composition is coated on a substrate with a chemical pattern, and annealed in an inert atmosphere or vacuum to obtain an ordered nanostructure perpendicular to the substrate and throughout the entire film thickness, and the nanostructure is transferred to the substrate by etching.

[0058] Preferably, in the present invention, the period of the chemical pattern in the substrate with the chemical pattern is n times the phase separation period of the high χ value block copolymer AbB, and n≥1, where n is an integer.

[0059] The source of the substrate with the chemical pattern is not particularly limited, and can be purchased or made by the self-made method including but not limited to EUV exposure, electron beam exposure, etc.

[0060] Preferably, the concentration of the solution of the polymer composition is 0.5wt%-10wt% in the present invention; more preferably, 2wt%-5wt%.

[0061] The solvent of the solution of the polymer composition includes, but is not limited to, one or more of toluene, propylene glycol methyl ether acetate, ethylene glycol methyl ether acetate, 1-methoxy-2-propyl acetate, chlorobenzene, and anisole.

[0062] Preferably, the annealing temperature is 60-270° C., and the annealing time is 2-1440 min;

[0063] The inert atmosphere includes but is not limited to nitrogen, argon and the like.

[0064] More preferably, in the present invention, the annealing temperature is 100-220° C. and the annealing time is 2-720 min under a nitrogen atmosphere.

[0065] Preferably, when the annealing is carried out under vacuum conditions, the annealing temperature is 60-250° C., and the annealing time is 5-1440 min; more preferably, the annealing temperature is 100-220° C., and the annealing time is 5-720 min.

[0066] In some specific embodiments of the present invention, a solution containing the above-mentioned polymer composition is coated on a silicon wafer modified with a molecular brush.

[0067] The coating is performed by spin coating, with a rotation speed of 2000-4000 rpm and a time of 15-60 s.

[0068] The guided self-assembly method of the present invention enables the block copolymer with high χ value and large difference in γ phase between the two blocks to obtain an ordered nanostructure perpendicular to the substrate and throughout the thickness of the film through patterned transfer. This is mainly because the additives in the polymer composition of the present invention migrate to the surfaces of the two phases during annealing, making the surface free energy of the block copolymer AbB with high χ value equal, thereby obtaining a vertical structure.

[0069] The additive of the present invention contains the same components as the high-χ value block copolymer AbB block, which can be better dispersed in the corresponding phase domain, better reduce the surface free energy gap between the segments, and obtain a nanostructure perpendicular to the substrate. The additive is a bottle brush polymer, which is different from traditional linear block copolymers. The main chain defines the phase separation interface, which is more conducive to phase separation and the formation of a surface film on the surface.

[0070] The invention obtains a vertical ordered nanostructure through a guided self-assembly method of a polymer composition composed of a relatively low content of additives, which is beneficial to the subsequent etching process, effectively shortens the process path, improves production capacity, and reduces costs.

[0071] The present invention has no particular limitation on the preparation methods of the high-χ value block copolymer AbB and additives I and II. Different synthesis methods can flexibly design the polymer structure and control the length of different side chains, which is more conducive to the formation of vertical structures.

[0072] Compared with the prior art, the polymer composition provided by the present invention comprises the following components, calculated by mass percentage: high χ value block copolymer AbB: 70wt%-99.8wt%; additive I: 0.1wt%-15wt%; additive II: 0.1wt%-15wt%; the sum of all components is 100wt%; the χ value of the high χ value block copolymer AbB is greater than 0.05, and the surface free energy of block A is γ A >30mJ / m 2 , the surface free energy of block B γ B >30mJ / m 2 The absolute value of the surface free energy difference between the two blocks is greater than 5 mJ / m 2 The number average molecular weight of the high χ value block copolymer AbB is 5k-50k, and the volume fraction of block A is 20%-80%; the additives I and II are polymers AC and BC, respectively, and the topological structures of both are bottle brush-like; the surface free energy of C in the polymers AC and BC is γ C <30mJ / m 2 And it does not react with A or B. The polymer composition of the present invention can obtain an ordered nanostructure perpendicular to the substrate and throughout the entire film thickness by guided self-assembly, and can transfer the nanostructure to the substrate by etching. This makes it easier for block copolymers with high χ values ​​and large difference in γ between the two blocks to obtain an ideal vertical ordered nanostructure, providing a new idea for obtaining a smaller substrate structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 A flow chart for guiding the self-assembly method of the present invention; Figure 2 Schematic diagram of guided self-assembly of the present invention, wherein 100 represents the C domain in additives Ⅰ and Ⅱ, 200 represents the polymer composition layer, 211 represents the A block domain, 212 represents the B block domain, 300 represents the chemical pattern layer, 400 represents the substrate layer, and 400' represents the substrate after etching; Figure 3 The vertically aligned nanostructure prepared in Example 1; Figure 4 The vertically aligned nanostructure prepared in Example 4; Figure 5 For the high χ value diblock copolymer PS- b- Assembly results of P2VP; Figure 6 It is a structural diagram, where a is A- stat -C or B- stat - schematic diagram of the structure of C, FIG. b is a schematic diagram of the structure of macromonomer A or macromonomer B, FIG. c is a schematic diagram of the structure of macromonomer C, ● represents a reactive group; Figure 7 It is a structural schematic diagram, where d is A- branch -C or B- branch -C structural diagram, Figure e is the macromolecular monomer A- b -C or macromonomer B- b -Structural diagram of C, ● represents a reactive group. DETAILED DESCRIPTION

[0078] In order to further illustrate the present invention, the guided self-assembly method of the polymer composition and the film thereof provided by the present invention is described in detail below with reference to the embodiments.

[0079] Example 1

[0080] Preparation of PtBS-b-P2VP, PPFS-stat-PtBS, and PPFS-stat-P2VP compositions and their guided self-assembly.

[0081] PtBS-b-P2VP, PPFS-stat-PtBS, and PPFS-stat-P2VP were all purchased. The number average molecular weight of PtBS-b-P2VP was 13.4k, the volume fraction of PS segments was 52%, and the molecular weight distribution was 1.10; the backbone chain length (or degree of polymerization) of PPFS-stat-PtBS was 20, the molecular weight of PPFS side chains was 4.8k, the molecular weight distribution was 1.14, the molecular weight of PtBS side chains was 5k, the molecular weight distribution was 1.10, and the volume fraction of PHFAS was 59%; the backbone chain length of PPFS-stat-P2VP was 20, the molecular weight of PPFS side chains was 4.8k, the molecular weight distribution was 1.14, the molecular weight of PS side chains was 5.3k, the molecular weight distribution was 1.08, and the volume fraction of PPFS was 58%;

[0082] (1) Preparation of polymer composition

[0083] 1 wt% of additive I PPFS-stat-PtBS, 1 wt% of additive II PPFS-stat-P2VP and high-χ block copolymer PtBS-b-P2VP were mixed to form a polymer composition, which was dissolved in toluene to prepare a 3.0 wt% composition solution.

[0084] (2) Guided autonomous assembly of vertical nanostructures A silicon wafer was used as a substrate. After cleaning, the wafer was exposed using an EUV lithography machine to obtain a two-dimensional chemical pattern substrate. 0.1 mL of the solution was spin-coated on the substrate with the chemical pattern at a spin-coating speed of 2500 rpm for 30 s. Annealing was performed at 180 °C for 30 min under vacuum conditions to obtain a block copolymer film. Figure 3 As shown, the high χ value block copolymer PtBS- b -P2VP assembles into a layered phase perpendicular to the silicon wafer that corresponds to the chemical pattern.

[0086] Example 2

[0087] Preparation of PS-b-P2VP, PDMS-branch-P2VP, and PDMS-branch-PS compositions and their guided self-assembly.

[0088] PS-b-P2VP, PDMS-branch-P2VP, and PDMS-branch-PS were purchased. The number average molecular weight of PS-b-P2VP was 47.5k, the volume fraction of PS segments was 56%, and the molecular weight distribution was 1.11; the backbone link length of PDMS-branch-P2VP was 5, the molecular weight of the macromonomer PDMS-b-P2VP was 19.3k, the molecular weight distribution was 1.12, and the volume fraction of PDMS was 47%; the backbone link length of PDMS-branch-PS was 5, the molecular weight of the macromonomer PDMS-b-PS was 17.5k, the molecular weight distribution was 1.10, and the volume fraction of PDMS was 49%;

[0089] (1) Preparation of polymer composition

[0090] 11 wt% of additive I PDMS-branch-P2VP, 14 wt% of additive II PDMS-branch-PS and high-χ block copolymer PS-b-P2VP are mixed to form a polymer composition. The composition is dissolved in propylene glycol methyl ether acetate to prepare a 2.0 wt% composition solution.

[0091] (2) Guided autonomous assembly of vertical nanostructures

[0092] A silicon wafer was used as a substrate. After cleaning, the wafer was exposed using an EUV lithography machine to obtain a two-dimensional chemical pattern substrate. 0.1 mL of the solution was spin-coated on a substrate with a chemical pattern at a speed of 4000 rpm for 30 seconds. The block copolymer film was annealed at 170 ° C for 30 minutes under vacuum conditions. The high-χ block copolymer PS-b-P2VP assembled into a layered phase corresponding to the chemical pattern perpendicular to the silicon wafer.

[0093] Example 3

[0094] PCHE-b-PMMA, C 18 H 37 -branch-PCHE,C 18 H 37 Synthesis of -branch-PMMA compositions and their guided self-assembly.

[0095] PCHE-b-PMMA, C 18 H 37 -branch-PCHE,C 18 H 37 -branch-PMMA were purchased, the number average molecular weight of PCHE-b-PMMA was 5k, the volume fraction of PCHE segment was 46%, and the molecular weight distribution was 1.11; C 18 H 37 -branch-PCHE backbone link length is 50, macromonomer C 18 H 37 -b-PCHE molecular weight is 1k, molecular weight distribution is 1.12; C 18 H 37 -branch-PMMA backbone link length is 50, macromonomer C 18 H 37 -b-PMMA has a molecular weight of 1k and a molecular weight distribution of 1.15;

[0096] (1) Preparation of polymer composition

[0097] 0.8 wt% of additive IC 18 H 37 -branch-PCHE, 1wt% Additive ⅡC 18 H 37 -branch-PMMA and high-χ block copolymer PCHE-b-PMMA are mixed to form a polymer composition. The composition is dissolved in propylene glycol methyl ether acetate to prepare a 5.0 wt% composition solution.

[0098] (2) Guided autonomous assembly of vertical nanostructures

[0099] A silicon wafer was used as a substrate. After cleaning, the wafer was exposed using an EUV lithography machine to obtain a two-dimensional chemical pattern substrate. 0.1 mL of the solution was spin-coated on a substrate with a chemical pattern at a speed of 3000 rpm for 30 seconds. The block copolymer film was annealed at 200 ° C for 300 minutes under vacuum conditions. The high-χ block copolymer PCHE-b-PMMA assembled into a layered phase corresponding to the chemical pattern perpendicular to the silicon wafer.

[0100] Example 4

[0101] PS-b-PPC, C 26 F 53 -stat-PS,C 26 F 53 Synthesis of -stat-PPC compositions and their guided self-assembly.

[0102] PS-b-PPC, C 26 F 53 -stat-PS,C 26 F 53 -stat-PPC was purchased, the number average molecular weight of PS-b-PPC was 18k, the volume fraction of PS chain segment was 30%, and the molecular weight distribution was 1.11; C 26 F 53 -stat-PS backbone chain length is 10, PS side chain molecular weight is 2k, molecular weight distribution is 1.08, and PS volume fraction is 81%; C 26 F 53 -stat-PPC backbone link length is 10, PPC side chain molecular weight is 2k, molecular weight distribution is 1.10, and volume fraction of PPC is 78%;

[0103] (1) Preparation of polymer composition

[0104] 1wt% of additive IC 26 F 53 -stat-PS, 2.5wt% Additive IIC 26 F 53 -stat-PPC and high-χ block copolymer PS-b-PPC are mixed to form a polymer composition. The composition is dissolved in propylene glycol methyl ether acetate to prepare a 1.0 wt% composition solution.

[0105] (2) Guided autonomous assembly of vertical nanostructures

[0106] A silicon wafer was used as a substrate. After cleaning, the wafer was exposed using an EUV lithography machine to obtain a two-dimensional chemical pattern substrate. 0.1 mL of the solution was spin-coated on the substrate with the chemical pattern at a spin-coating speed of 2500 rpm for 30 seconds. The block copolymer film was annealed at 150 ° C for 30 minutes under vacuum conditions. The high-χ block copolymer PS-b-PPC assembled into a columnar phase corresponding to the chemical pattern perpendicular to the silicon wafer, such as Figure 4 shown.

[0107] Example 5

[0108] PS-b-P4VP,C 20 F 41 -stat-PS,C 20 F 41 Synthesis of -stat-P4VP compositions and their guided self-assembly.

[0109] PS-b-P4VP,C 20 F 41 -stat-PS,C 20 F 41 -stat-P4VP were purchased, PS-b-P4VP number average molecular weight was 15k, the volume fraction of PS segment was 51%, and the molecular weight distribution was 1.10; C 20 F 41 -stat-PS backbone link length is 5, PS side chain molecular weight is 3k, molecular weight distribution is 1.08, and PS volume fraction is 89%; C 20 F 41 -stat-P4VP backbone link length is 5, P4VP side chain molecular weight is 3k, molecular weight distribution is 1.09, and volume fraction of P4VP is 88%;

[0110] (1) Preparation of polymer composition

[0111] 2wt% of additive IC 20 F 41 -stat-PS, 2wt% Additive IIC 20 F 41 -stat-P4VP and high-χ block copolymer PS-b-P4VP are mixed to form a polymer composition. The composition is dissolved in propylene glycol methyl ether acetate to prepare a 1.0 wt% composition solution.

[0112] (2) Guided autonomous assembly of vertical nanostructures

[0113] A silicon wafer was used as a substrate. After cleaning, the wafer was exposed using an EUV lithography machine to obtain a two-dimensional chemical pattern substrate. 0.1 mL of the solution was spin-coated on a substrate with a chemical pattern at a speed of 4000 rpm for 30 seconds. The block copolymer film was annealed at 170 ° C for 30 minutes under vacuum conditions. The high-χ block copolymer PS-b-P4VP assembled into a layered phase corresponding to the chemical pattern perpendicular to the silicon wafer.

[0114] Comparative Example 1

[0115] Assembly of high-χ block copolymer PS-b-P2VP (PS-b-P2VP number average molecular weight is 17.3k, the volume fraction of PS segment is 51%, and the molecular weight distribution is 1.10) on a non-neutral substrate.

[0116] The high-χ block copolymer PS-b-P2VP was dissolved in DMF to prepare a 1.5 wt% solution. 0.1 mL of the toluene solution was spin-coated on a substrate with a chemical pattern at a spin-coating speed of 4000 rpm for 30 seconds. The solution was annealed at 160°C for 30 minutes under a nitrogen atmosphere. A phase-separated block copolymer film was obtained, such as Figure 5 As shown. Figure 5 It can be seen that the self-assembly results show an island-hole structure, and no vertically arranged structure is formed. This indicates that in the absence of block copolymer additives, the high χ value block copolymer PS-b-P2VP is difficult to form a vertically arranged structure.

[0117] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A polymer composition, characterized in that Calculated by mass percentage, it includes the following components: High χ value block copolymer AbB: 70wt%-99.8wt%; Additive I: 0.1wt%-15wt%; Additive II: 0.1wt%-15wt%; The sum of all components is 100wt%; The high-χ value block copolymer AbB has a χ value>0.05, and the surface free energy of block A is γ A >30mJ / m 2 , the surface free energy of block B γ B >30mJ / m 2 The absolute value of the surface free energy difference between the two blocks is greater than 5 mJ / m 2 ; The high-χ value block copolymer AbB has a number average molecular weight of 5k-50k, and a volume fraction of block A of 20%-80%; The additives I and II are polymers AC and BC, respectively, and both have bottle-brush-like topological structures; The surface free energy of C in the polymers AC and BC is γ C <30mJ / m 2 And it does not react with A or B.

2. The polymer composition according to claim 1, characterized in that The high-χ value block copolymer AbB is selected from one or more of polystyrene derivative-b-polyvinyl pyridine, polystyrene derivative-b-polyacrylate derivative, polyvinyl condensed ring-b-polyacrylate derivative, and polyvinyl alicyclic-b-polyacrylate derivative.

3. The polymer composition according to claim 2, characterized in that The high x value block copolymer AbB is selected from one or more of polystyrene-b-poly(2-vinylpyridine), poly(4-tert-butylstyrene)-b-poly(2-vinylpyridine), polystyrene-b-poly(4-vinylpyridine), polystyrene-b-polycarbonate acrylate, polystyrene-b-polyglycerol monomethyl methacrylate, polymethylstyrene-b-polymethyl methacrylate, polydimethylstyrene-b-polymethyl methacrylate, poly-4-vinylbiphenyl-b-polymethyl methacrylate, polymethylstyrene-b-polymethyl acrylate, polydimethylstyrene-b-polymethyl acrylate, poly-4-vinylbiphenyl-b-polymethyl acrylate, polyvinylnaphthalene-b-polymethyl methacrylate, and polycyclohexylethylene-b-polymethyl methacrylate.

4. The polymer composition according to claim 1, characterized in that The C in the polymers AC and BC is selected from fluorine-containing polymers, silicon-containing polymers, 16 -C 32 Alkanes or C 10 -C 32 of perfluorinated alkanes.

5. The polymer composition according to claim 1 or 4, characterized in that The polymer AC is selected from A-stat-C or A-branch-C; the polymer BC is selected from B-stat-C or B-branch-C; C in the polymer AC and the polymer BC is selected from a fluorine-containing polymer or a silicon-containing polymer; the backbone chain polymerization degree of the A-stat-C and B-stat-C is independently selected from 2-50, wherein the number average molecular weights of the macromonomer A, the macromonomer B and the macromonomer C are independently selected from 1k-10k, and the volume fraction of C in the polymer A-stat-C or B-stat-C is 30%-70%; The backbone chain polymerization degrees of A-branch-C and B-branch-C are independently selected from 2-50, wherein the number average molecular weight of the macromonomer AbC or BbC is independently selected from 1k-20k, and the volume fraction of C in A-branch-C and B-branch-C is 30%-70%.

6. The polymer composition according to claim 1 or 4, characterized in that The polymer AC is selected from A-stat-C or A-branch-C; the polymer BC is selected from B-stat-C or B-branch-C; The C in the polymer AC and the polymer BC is selected from C 16 -C 32 Alkanes or C 10 -C 32 Perfluoroalkanes; The backbone chain polymerization degree of A-stat-C and B-stat-C is independently selected from 2-50, wherein the number average molecular weight of macromonomer A and macromonomer B is independently selected from 1k-10k, and the volume fraction of C in polymer A-stat-C or B-stat-C is 1%-40%; The backbone chain polymerization degrees of A-branch-C and B-branch-C are independently selected from 2-50, wherein the number average molecular weight of the macromonomer AbC or BbC is independently selected from 1k-10k.

7. The polymer composition according to claim 4, characterized in that The fluorine-containing polymer is selected from one or more of polypentafluorostyrene, polyperfluoroalkyl methacrylate, and polyperfluoroalkyl acrylate; The silicon-containing polymer is selected from one or more of polydimethylsiloxane, polymethylphenylsiloxane, poly(4-trimethylsilylstyrene), poly(dimethylsiloxane-co-methylphenylsiloxane), poly(dimethylsiloxane-co-diphenylsiloxane), and polymethylphenylsiloxane.

8. The polymer composition according to claim 4, characterized in that The alkane is selected from C 16 -C 32 Alkanes with an even number of C; The perfluoroalkane is selected from C 10 -C 32 A perfluoroalkane wherein the number of C is an even number.

9. A method for guided self-assembly of a polymer composition film, characterized in that: The following steps are involved: Coating a solution containing the polymer composition according to any one of claims 1 to 8 on a substrate with a chemical pattern, annealing in an inert atmosphere or vacuum to obtain an ordered nanostructure perpendicular to the substrate and throughout the entire thickness of the film, and transferring the nanostructure to the substrate by etching; The period of the chemical pattern in the substrate with the chemical pattern is n times the phase separation period of the high-χ value block copolymer AbB, and n≥1, where n is an integer.

10. The guided self-assembly method according to claim 9, characterized in that: The annealing temperature is 60-270° C., and the annealing time is 2-1440 min.